2015
DOI: 10.2147/cia.s70313
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in elderly patients: a systematic review

Abstract: Controversy exists regarding the effectiveness and safety of bariatric/metabolic surgery in elderly patients. We performed a systematic review on this issue in patients aged 60 years or older. MEDLINE, Cochrane Library, Embase, Scopus, and Google Scholar were searched until August 2015 for studies on outcomes of bariatric surgery in elderly patients. The results were expressed as pooled proportions (%) with 95% confidence intervals. Heterogeneity across the studies was evaluated by the I2 test, and a random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 58 publications
3
39
0
2
Order By: Relevance
“…In earlier times, several national and international guidance's recommended that weight loss surgical interventions should be restricted to patients under 60 years old based on the concerns of age-related increased surgical risks ( 27 ). Nonetheless, as the amount of clinical evidence enlarged, it became recognizable that the surgical outcomes of bariatric surgery, including morbidity and mortality rates, in older patients were not significantly different than those observed in younger ones ( 28 31 ). Thus, the number of bariatric procedures performed in older patients has increased over the past decades ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier times, several national and international guidance's recommended that weight loss surgical interventions should be restricted to patients under 60 years old based on the concerns of age-related increased surgical risks ( 27 ). Nonetheless, as the amount of clinical evidence enlarged, it became recognizable that the surgical outcomes of bariatric surgery, including morbidity and mortality rates, in older patients were not significantly different than those observed in younger ones ( 28 31 ). Thus, the number of bariatric procedures performed in older patients has increased over the past decades ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older age is a predictor of increased length of hospital stay, although there is no significant increase in mortality. This has been shown in studies that found individuals over 65 to be most likely to require prolonged hospitalization 25 , 26 . Robert et al .…”
Section: Discussionmentioning
confidence: 76%
“…In bariatric surgery, however, this is considered a valuable diagnostic tool. When compared to international literature, the number of serious complications was significantly lower in DATO [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 92%
“…Bariatric procedures were considered relatively safe, regarding to other surgical interventions, where mortality and morbidity were considered acceptable [ 1 , 4 , 31 , 32 ]. With 16 deaths out of 21,634 unique patients in the past 2 years, bariatric surgery in the Netherlands can be considered relatively safe.…”
Section: Discussionmentioning
confidence: 99%